Pole raising and speech making : modalities of Swedish-American summer celebration - Attebery, Jennifer Eastman, 1951- (University Press of Colorado, 2015)
"Focused on the beginnings of the traditional Scandinavian Midsummer celebration and the spring-to-summer seasonal festivities in the Rocky Mountain West during the height of Swedish immigration. Combines folklore and history, to explore various ways Midsummer-related celebrations blended with the American 4thth of July and the Mormon Latter Day Saint Pioneer Day on July 24th"-- Provided by publisher
Keywords: Festivals -- Rocky Mountains Region.; Holidays -- Rocky Mountains region.; Folklore -- Rocky Mountains.; Swedish Americans -- Rocky Mountains region -- Social life and customs.; Rocky Mountains Region -- Social life and customs.; West (U.S.) -- Social life and customs.; Folklore -- Rocheuses, Montagnes.; États-Unis (Ouest) -- Mœurs et coutumes.; SOCIAL SCIENCE/Holidays (non-religious); SOCIAL SCIENCE -- General.; Festivals; Folklore; Holidays; Manners and customs; Swedish Americans -- Social life and customs; Rocky Mountains; Rocky Mountains Region; West United States